2015
DOI: 10.1093/jac/dkv380
|View full text |Cite|
|
Sign up to set email alerts
|

Phase 3 pharmacokinetics and safety study of a posaconazole tablet formulation in patients at risk for invasive fungal disease

Abstract: In patients at high risk for invasive fungal disease, 300 mg posaconazole (as tablets) once daily was well tolerated and demonstrated a safety profile similar to that reported for posaconazole oral suspension: most patients (99%) achieved steady-state pCavg exposures >500 ng/mL and only one patient (<1%) had a pCavg <500 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
125
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(154 citation statements)
references
References 20 publications
15
125
2
12
Order By: Relevance
“…It is important to note that the primary liver injury observed was hyperbilirubinemia, which is frequently multifactorial in this population and may reflect physiological phenomena rather than drug-induced liver injury (22,23). As a more specific marker of drug-induced liver injury, grade 3 or 4 elevations in ALT levels were observed in only 2% of patients without preexisting liver injury and 5% of patients with such abnormalities, similar to findings observed in the phase 3 clinical trial of PCZ tablets (9). Furthermore, because this was a retrospective study, a cause-effect relationship between serum PCZ levels and liver injury cannot be established or presumed.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is important to note that the primary liver injury observed was hyperbilirubinemia, which is frequently multifactorial in this population and may reflect physiological phenomena rather than drug-induced liver injury (22,23). As a more specific marker of drug-induced liver injury, grade 3 or 4 elevations in ALT levels were observed in only 2% of patients without preexisting liver injury and 5% of patients with such abnormalities, similar to findings observed in the phase 3 clinical trial of PCZ tablets (9). Furthermore, because this was a retrospective study, a cause-effect relationship between serum PCZ levels and liver injury cannot be established or presumed.…”
Section: Discussionsupporting
confidence: 70%
“…The tablet and intravenous formulations were approved on the basis of safety and pharmacokinetic data, with corresponding phase III data for the tablet formulation recently being published (9). To date, several small, single-center studies have reviewed the initial implementation of PCZ tablets, focusing mainly on pharmacokinetic endpoints (5,6,(10)(11)(12).…”
mentioning
confidence: 99%
“…54,59 In a recent study, Cornely et al found that 90% of adult patients taking the newer delayed release tablets for prophylaxis of fungal infections had steady-state trough levels >700 ng/mL and there was no correlation between drug levels and adverse events. 60 Thus, TDM is unlikely to provide clinical benefit to patients taking the delayed release formulation of posaconazole for prophylaxis of fungal infections. It is not yet clear whether there will be a role for TDM in patients taking posaconazole for treatment of invasive fungal disease.…”
Section: Isavuconazonium Sulfatementioning
confidence: 99%
“…A Phase III multicenter trial used the 300-mg delayed-release posaconazole oral tablet to further examine the pharmacokinetics in AML or myelodysplasia patients along with recent HSCT recipients [30]. During the 28-day trial period, the predefined steady-state concentration goal, set at 0.50–3.75 mg/l, was achieved in 96% of patients, with 81% falling in the range between 0.50 and 2.50 mg/l.…”
Section: Pharmacologymentioning
confidence: 99%